In vitro mimicking the morphology of hepatic lobule tissue based on Ca-alginate cell sheets. (21st February 2018) - Liu, Zeyang; Lu, Minmin; Takeuchi, Masaru; Yue, Tao; Hasegawa, Yasuhisa; Huang, Qiang; Fukuda, Toshio
Abstract: Artificial cell sheets are commonly utilized as buiding blocks for tissue engineering. We propose a novel approach in the fabrication of Ca-alginate gel sheets, embedded with liver cells (RLC-18) in order to mimic liver lobule tissue. Ca-alginate sheets with hepatic lobule-shaped patterns were deposited onto a micro-electrode device using electrodeposition. Viability of embedded cells was ensured to exceed 80%. Cell morphology and biofunctionality were monitored during the one-week culture period and results compared with those of traditional 2D culture. In addition, we detached cell sheets from the electrode substrate and stacked them into a 3D multi-layered structure to mimic the morphology of liver lobule tissue.